Feeling Good in Your Own Skin: The Influence of Complimentary Sexual Stereotypes on Risky Sexual Attitudes and Behaviors in a Community Sample of African American Women - Duvall, Jamieson L. (2013)
Although negative racial stereotypes may affect the mental and physical health of African Americans, little research has examined the influence of positive or complimentary racial stereotypes on such outcomes. More specifically, this study explored the relationship between African American women’s endorsement of complimentary stereotypes about their sexuality (CSS) and attitudes/behaviors that have been associated with sexual risk. Data were gathered from 206 African American women as part of the Black Women in the Study of Epidemics project (B-WISE). Multivariate regression models were used to examine associations between women’s endorsement of CSS and selected sex-related attitudes and behaviors. Participants’ endorsement of CSS was significantly positively associated with beliefs that having sex without protection would strengthen their relationship (B = .28, SE = .10, p < .01) and that they could use drugs and always make healthy choices about using protection (B = .31, SE = .09, p < .01). Significant positive associations were also found between CSS and the number of casual sexual partners women reported in the past year (B = .29, SE = .15, p = .05) and their willingness to have sex in exchange for money or drugs during that time (B = .78, OR = 2.18, p < .05). These findings suggest that endorsement of CSS by African American women can lead to increased risk behavior, particularly relating to possible infection with HIV or other sexually transmitted infections (STI).